Ethics - Roth, John K. (Pasadena, Calif. : Salem Press, 2005)
Applied ethics is the main focus of this revised edition, with a particular emphasis on current ethics issues. Includes religious issues, business and labor ethics, political and economic issues, personal and social ethics issues, and bioethics.
Vol. 1. Abelard, Peter-Genocide, frustration-aggression theory of -- Vol. 2. Genocide and democide -- Power -- Vol. 3. Practical reason -- Zoroastrian ethics -- Index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Ethics -- Encyclopedias; Morale -- Encyclopédies.; PHILOSOPHY -- Social; PHILOSOPHY -- Ethics & Moral Philosophy; Ethics; encyclopedias; Encyclopedias; Encyclopedias; Encyclopédies.